Pobożność maryjna w ujęciu Josepha Ratzingera/ Benedykta XVI - Borto, Paweł (Verbum Vitae, 2024)
The article presents an understanding of Marian devotion and its theological justification as seen by Joseph Ratzinger/Benedict XVI. The basis for the analyses carried out was primarily systematic Mariological texts, as well as selected statements of Benedict XVI. The analysis carried out showed that the issue of Marian devotion to J. Ratzinger is closely connected with Mariological reflection. This Mariological reflection he always developed in close connection with the mystery of Revelation and with the right balance between christotypical and ecclesiotypical Mariology. At the same time, there was a certain change in Ratzinger’s views on the role of Marian devotion. The initial distance from certain forms of Marian devotion gave way to an attitude of appreciation for this devotion. The conclusions of the analysis allow us to summarize that the model of Marian piety proposed by Ratzinger is closely connected with the logic of Revelation and authentic reverence for God, flows from the reading of Scripture, remains faithful to the content of Marian dogmas, and points to Mary as the perfect disciple of the Lord and the personification of the Church. While these conclusions have already been indicated in other publications, it should be emphasized that a certain evolution must be taken into account in the views of the Bavarian theologian. While a certain constancy characterizes these views, over time, greater attention to the practice of Marian devotion emerges in his work. It is seen not only as an expression of obedience to the words of Scripture (cf. Luke 1:48), but brings a personal dimension to experiencing the mystery of God and the Church, allowing one to appreciate local traditions and veneration shown to Mary, and teaches that an encounter with God also demands the involvement of the heart.